Press History Framework for A Press History Course - Febbrizal, F; Abdurakhman, A (Universitas Muhammadiyah Surakarta, 2023)
The study of press history is a subsection of universal history that is studied and used as a patron in writing and teaching history. The study of press history is not only thematic and refers to the methodological part of research (as a primary source) but also has a unique performance to be taught at the college level and below. The research method used in this book is a literature study; the first part is collecting press history sources; the second is sorting and selecting press history; and the third is reviewing and analyzing the container that becomes the framework of Indonesian press history. This research found a suitable platform in the authorship, what is referred to as the